Roles of eco-friendly non-edible vegetable oils in drilling inconel 718 through minimum quantity lubrication - Nur Syahilia Syahira, Safie; Muhamad Nasir, Murad; Lih, Tan Chye; Azwan Iskandar, Azmi; Wan Azmi, Wan Hamzah; Mohd, Danish (MDPI, 2022)
Metal cutting fluids (MCFs) have played a principal role as coolants and lubricants in the machining industry. However, the wide use of mineral-based oil MCFs has contributed to an adverse effect on humans and the environment. Thus, to overcome the adverse effects of mineral-based oil MCFs, eco-friendly vegetable oil, which is non-edible oil, has been implemented to overcome the issues related to edible oil such as manufacturing costs and food shortages. This study investigated the performance of three different types of non-edible oil, namely castor, neem, and rice bran oils in drilling Inconel 718 using a coated titanium aluminum nitride (TiAlN) carbide drill towards tool life, tool wear, surface integrity, dimensional accuracy, and chip thickness. The MCFs were implemented under the minimum quantity lubrication (MQL) condition at a 50 mL/h flow rate using different cutting speeds (10, 20 m/min) and a constant feed (0.015 mm/rev). The results showed that castor oil minimizes the rapid growth of tool wear and prolongs the tool life by 50% at 10 m/min as compared to rice bran oil. At 20 m/min, castor oil obtained the lowest values of average surface roughness (1.455 µm) and chip thickness (0.220 mm). It was also found that different cutting speeds did not contribute to any significant trend towards hole diameter and roundness for all MCFs. The outstanding performance of castor oil proved that the oil is a potential alternative as an eco-friendly MCF for a cleaner machining environment. Castor oil was determined to be optimum in terms of tool life, tool wear, surface roughness, and chip thickness.